Modeling and evaluation of trust in cloud computing environments - Qiang Guo; Dawei Sun; Guiran Chang; Lina Sun; Xingwei Wang (2011 3rd International Conference on Advanced Computer Control, 2011)
Today, one of the most important factors for the success of cloud computing is to create trust and security. Cloud computing will face a lot of challenges when the key element trust is absent. There are no special trust evaluation models for cloud computing environment. In this paper, the definition of trust in cloud systems is introduced and the properties of trust are analyzed. Based on the properties and semantics of trust, an extensible trust evaluation model named ETEC is proposed, which includes a time-variant comprehensive evaluation method for expressing direct trust and a space-variant evaluation method for calculating recommendation trust. To compute trust in cloud systems, an algorithm based on the ETEC model is given. Simulation and analysis shows that this model can calculate the trust degree effectively and reasonably in cloud computing environments.